Top-down effects of an exotic serpulid polychaete on natural plankton assemblage of estuarine and brackish systems in the SW Atlantic - Pan, Jeronimo (2014)
The invasive reef-building polychaete Ficopomatus enigmaticus (Fauvel, 1923) has become well-established in many temperate brackish waters. To analyze preferences for different planktonic food sources, short-term (~1.5 h), grazing microcosm experiments were performed in situ (n ¼ 3), at two water bodies, a coastal lagoon (Mar Chiquita, MC) and the mixohaline stretches of a coastal creek (La Tigra, LT), Argentina, in January 2007. Relative clearance rates of phytoplankton were assessed for chlorophyll a size-fractions and for different groups of nanoplanktonic and microplanktonic protists. The two locations showed significant differences in plankton community structure. Nanoeukaryotes were the dominant group at both locations; the second most-abundant groups were diatoms at MC and ciliates at LT. There were significant differences in chlorophyll-based clearance rates in relation to phytoplankton size-fraction. Clearance rates for pennate diatoms were significantly higher than for any other planktonic prey (2.3 l h1 g DW1 ). Ficopomatus enigmaticus presented relatively high clearance rates for heterotrophic ciliates (1.5 l h1 g DW1 ). Biomass removal by F. enigmaticus was high (.50% of initial standing stocks for all components), indicating that the serpulid was capable of regulating planktonic biomass. Significant differences in clearance for different components of the community suggest that F. enigmaticus has the potential to promote changes in plankton community structure and, hence, exerts strong top-down controls.